Un retour en actualité de la notion de démarche dispositive ? - Geneviève Lameul (Centre National d'Enseignement à Distance, 2015)
This paper highlights the concept of systemic approach developed by Geneviève Jacquinot and Hugues Choplin in 2002. This concept, at the crossroads between innovation and computing systems can be seen in the context of other forms of research most often considered today as cooperative engineering or design based research. Written from a very personal point of view based on the experience of the author, the article questions the cumulativity of research results and also the links and bridges to build to access better understandability of increasingly complex situations. It specifies the different situations where research and action are present and intersect and enlighten each other, and questions the postures of the actors in each configuration.